2011
DOI: 10.1590/s1984-70332011000500009
|View full text |Cite
|
Sign up to set email alerts
|

Germplasm enhancement for adaptation to climate changes

Abstract: -Billions of dollars and crops

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…These results corroborate those of Joshi and Bauer (2006) and Napasintuwong and Pray (2014) who also found that early maturity significantly affects adoption of improved varieties. The significant effect of yield potential on adoption of Apomuden is also in line with prior findings ( Carena, 2011 ), especially given that Northern Ghana has a unimodal rainy season distribution pattern.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results corroborate those of Joshi and Bauer (2006) and Napasintuwong and Pray (2014) who also found that early maturity significantly affects adoption of improved varieties. The significant effect of yield potential on adoption of Apomuden is also in line with prior findings ( Carena, 2011 ), especially given that Northern Ghana has a unimodal rainy season distribution pattern.…”
Section: Discussionsupporting
confidence: 90%
“…These results corroborate those of Joshi and Bauer (2006) and Napasintuwong and Pray (2014) who also found that early maturity significantly affects adoption of improved varieties. The significant effect of yield potential on adoption of Apomuden is also in line with prior findings (Carena, 2011), especially given that Northern Ghana has a unimodal rainy season distribution pattern. The significant and negative coefficients of early maturity, disease resistance, yield potential, and ease of establishing with scarce rains in the Obare model imply that the farmers found these attributes of Obare inferior as compared to those of Apomuden.…”
Section: The Role Of Other Varietal Attributes In the Adoption Of Ofspsupporting
confidence: 88%
“…We found the SS x non-SS heterotic pattern to be frequent in our trials representing short-season ex-PVP and current industry genetic materials, in agreement with Mikel and Dubley (2006). Further sampling for larger genetic diversity , Carena 2011, Sharma and Carena 2012) is needed to develop alternative and productive heterotic patterns. Integration of exotic germplasm improvement with inbred line development has produced NDSU inbred lines associated with different heterotic groups.…”
Section: Heterotic Pattern Detectionmentioning
confidence: 99%
“…Germplasm carrying unique genes can break environmental margins (Carena, 2011). However, Brown (1953) pointed out that farmers utilized only 2% of the world's maize germplasm after hybrids dominated the maize production market.…”
Section: Introductionmentioning
confidence: 99%